THE USE OF DIGITAL STORYTELLING (DST) IN TEACHING SPEAKING - Maizal Asriati; Ferlya Elyza; Rini Susiani (Fakultas Teknik Universitas Negeri Makassar, 2025)
This research aims to explore the use of Digital Storytelling in enhancing English speaking skills. Using a quantitative approach, the study employed a pre-experimental design with pre-test and post-test assessments. According to Sugiyono (2015), quantitative research involves concrete data measured with statistical methods. The sample consisted of 25 first-grade students from SMAN 4 Banda Aceh, selected through random sampling. Results revealed a significant improvement in speaking skills, with pre-test scores averaging 42 and post-test scores averaging 79. The paired samples t-test showed a Sig. value of 0.000, indicating a highly significant difference. These findings suggest that Digital Storytelling is an effective tool for improving students' speaking skills. Despite limitations such as a small sample size and lack of a control group, the study highlights the practical benefits of incorporating Digital Storytelling into the curriculum. Future research should further investigate the long-term effects and mechanisms behind Digital Storytelling's impact on language learning.